Its Congenital Hepatic Fibrosis; Not Cirrhosis At All - Shrestha, Ananta; Al-Mahtab, Mamun; Rahman, Salimur; Sarkar, Jahangir; Lama, Thupten K (Nepalese Medical Journal, 2018)
Congenital hepatic fibrosis is a rare condition characterized by extensive fibrosis of liver but with preserved normal lobular architecture inherited as autosomal recessive trait. We report a 19 year-old-female admitted to Bangabandhu Sheikh Mujib Medical University with the complaints of lump in upper abdomen since last 13 years and episodes of fever and abdominal pain for same duration. She was diagnosed with hepatic TB on hepatic histology. Congenital hepatic fibrosis is a rare cause of portal hypertension that presents during childhood. Prognosis of congenital hepatic fibrosis is good. Life threatening events in these patients are related with variceal bleeding and episodes of cholangitis. Owing to relatively good liver function these patients tolerate portosystemic shunt surgeries quite well.Though rare, congenital hepatic fibrosis should be included in the differential diagnosis of portal hypertension in early life.